Examining the Effects of Construction Project Delays on Costs from the Perspective of Stakeholders Using a System Dynamics Approach: Insights from a Commercial Complex Project in Qom - Amirhosein Saffarinia; Hamidreza Yazdani (مدیریت صنعتی)
Objective Project delays are a prevalent issue in construction projects, particularly in Iran. The project schedule is established and approved after signing the contract and designing the plans, however, most of the project managers cannot complete the project on time and projects often overrun their scheduled completion dates. Generally speaking, the project is "delayed". Various factors contribute to these delays, and extensive research has been conducted to explore their causes. Disagreements between contractors and employers over the causes of delays often result in disputes and negotiations regarding costs and accountability. Consequently, delays are generally a costly problem. In some cases, it has been observed that delays may not be costly for all parties involved and can create conflicts of interest. In addition, project delays have many varied effects that increase the complexity of the problem. When explaining the cause-and-effect relationships of delay impacts, the System Dynamics model illustrates the outcomes of management decisions related to these delays. This paper aims to examine the consequences of construction projects’ delays and the relationships between them from the perspectives of various stakeholders.